Powerful Pulsed Plasma Generators Research and Application - Kolikov, Victor (Springer Series on Atomic, Optical, and Plasma Physics,, 2018)
This book presents experimental and theoretical results on extremely powerful plasma generators. It addresses pulsed electrical mega-ampere arcs and the mechanisms of energy transfer from the arc into hydrogen, helium and air under pressures up to 250 MPa and currents up to 2 MA. Extreme plasma parameters and increased energy density in the arc were achieved. It was found experimentally that increasing the initial gas pressure to hundreds of MPa leads to improved arc stability, high efficiency of energy transfer from arc to gas, and plasma enthalpy growth. The data obtained data provides the basis for the development of electrophysical devices with high energy density, e.g. high intensity sources for visible, UV and X-ray irradiation for laser pumping, generators of high enthalpy plasma jets, and plasma chemical reactors.